1994
DOI: 10.1164/ajrccm.150.6.7952608
|View full text |Cite
|
Sign up to set email alerts
|

Determination of humoral immunoglobulins M and G directed against mycobacterial antigen 60 failed to diagnose primary tuberculosis and mycobacterial adenitis in children.

Abstract: The serodiagnosis of primary tuberculosis (TB) and mycobacterial adenitis in children was tried using the Anda-Tb tests (Anda Biologicals, France) that measure immunoglobulins (Ig) M and G directed against mycobacterial antigen 60 (A60) by enzyme-linked immunosorbent assay. The 188 cases studied included 81 healthy or mycobacteria-unrelated diseased children with no reaction to tuberculin skin test (STN); 9 recent BCG vaccination (BCG); 35 asymptomatic (AsTB), 29 symptomatic (STB) primary TB and 11 adenitis ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Overall, Ab responses to mycobacterial antigens in childhood TB varied widely, with sensitivities and specificities ranging from 14% to 85% and from 86% to 100%, respectively. Even when evaluating the same commercially available test, such as the Anda-TB Kit (Anda Biologicals, Strasbourg, France), sensitivities for detecting childhood TB ranged from 14% to 71% and specificities ranged from 50% to 100%, with part of the variability being due to the different isotypes tested (22,24,29,66,67) (Table 1). Such wide ranges in accuracy of serologic assays have also been observed in adult TB, although many of the reasons for this variability differ (reviewed in references 62 to 64).…”
Section: Serologic Studies Evaluating the Diagnostic Value Of Antibodmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, Ab responses to mycobacterial antigens in childhood TB varied widely, with sensitivities and specificities ranging from 14% to 85% and from 86% to 100%, respectively. Even when evaluating the same commercially available test, such as the Anda-TB Kit (Anda Biologicals, Strasbourg, France), sensitivities for detecting childhood TB ranged from 14% to 71% and specificities ranged from 50% to 100%, with part of the variability being due to the different isotypes tested (22,24,29,66,67) (Table 1). Such wide ranges in accuracy of serologic assays have also been observed in adult TB, although many of the reasons for this variability differ (reviewed in references 62 to 64).…”
Section: Serologic Studies Evaluating the Diagnostic Value Of Antibodmentioning
confidence: 99%
“…Thus, similar to studies with PPD or mycobacterial sonicates, studies with A60-based assays evaluate serological responses to a broad mixture of mainly nonspecific native mycobacterial antigens, which may result in considerable cross-reactivity. Five studies have evaluated IgG, IgA, and IgM responses to A60 in children using the Anda-TB kit, with reported sensitivities ranging from 14% to 71% and specificities ranging from 50% to 100% (22,24,29,66,67) (Table 1).…”
Section: Mycobacterial Antigens Evaluated For Serodiagnosis In Childhmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of these antigens has resulted in a much higher sensitivity and specificity in cell response assays [23]. However, serological tests based on mycobacterial antigens to detect circulating antibodies have been hampered by decreased sensitivity and cross-reactivity with other mycobacteria [24][25][26][27][28], or have relatively limited utility in the diagnosis of TB in countries where TB is endemic [29]. Several molecular biological techniques have been proposed as indicators of disease activity in pulmonary and extrapulmonary TB [30,31] and are currently the most sensitive and specific diagnostic tests.…”
mentioning
confidence: 99%
“…Many studies have used this antigen and found almost 100% specificity [42], with sensitivity ranging from 68 to 91% [43, 85]. Unfortunately, this molecule has also been found in nonpathogenic Nocardia and Corynebacterium species [83].…”
Section: Human Tuberculosismentioning
confidence: 99%